Initial Preference for Labor Without Neuraxial Analgesia and Actual Use: Results from a National Survey in France. (September 2015) - Kpéa, Laure; Bonnet, Marie-Pierre; Le Ray, Camille; Prunet, Caroline; Ducloy-Bouthors, Anne-Sophie; Blondel, Béatrice
Abstract : BACKGROUND: The rate of neuraxial analgesia during labor in France is one of the highest among high-income countries: 77% of vaginal deliveries in 2010. In this context, the question of how women's preferences for delivering without neuraxial analgesia relate to actual use is of interest. Our objective was to study the factors associated with women's initial preference for labor without neuraxial analgesia and those associated with its use in women who initially preferred not to have it. METHODS: We used data from the 2010 French National Perinatal Survey, a cross-sectional study of a representative sample of all births in France. Data were collected from interviews with mothers in the postpartum ward and from medical records. Our sample included 7123 women who had vaginal deliveries and were at low risk for cesarean delivery. The factors analyzed were maternal sociodemographic characteristics, prenatal care, childbirth class attendance, labor management, and organization of maternity units. Multilevel Poisson regression models were used to study factors associated with women's initial preference in the overall population and to study factors associated with actual use of neuraxial analgesia in the group of women who initially preferred not to have it. RESULTS: Initially, 26% of our population ( n = 1835) preferred to deliver without neuraxial analgesia; this preference was associated with high parity, unfavorable social conditions, and delivery in a public maternity unit. Among these women, 52% ( n = 961) delivered with neuraxial analgesia. This discrepancy between initial preference and actual use was significantly associated with nulliparity (adjusted relative risk [aRR] = 1.4; 95% confidence interval [CI], 1.3–1.6), oxytocin augmentation of labor (aRR = 2.4; 95% CI, 2.1–2.7), presence of an anesthesiologist in the unit 24/7 (aRR = 1.4; 95% CI, 1.2–1.6; compared with delivery in hospitals without an anesthesiologist on site 24/7), and high midwife workload (aRR = 1.1; 95% CI, 1.0–1.2). There was no clear association with maternal educational level. CONCLUSIONS: Our results suggest that parity, the management of labor, and availability of anesthesiologists play a major role in the intrapartum decision to use neuraxial analgesia for women who initially preferred not to have it. Further research is necessary in the clinical circumstances leading to this decision and the role of women's demands and medical staff attitudes throughout labor. Abstract : Published ahead of print June 17, 2015